PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV MI AL-MUHAJIRIN MENGGALA SAKTI - Herlinawati, Herlinawati; Alpusari, Mahmud; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Problem Research is low results Students learn science class IV MI Al Muhajirin Menggala sakti That is an average of 57.75 With The KKM 70. This about caused teachers Still Less Varies in using Model Or development strategi in proces’s Learning that Students involved resuld Less Active While studying. This research in Shape Classroom Action Research (PTK). This research aims to improve learning IPA IV MI Al-Muhajirin Menggala Sakti. The formulation of the problem "Does the Model application of Quantum Teaching can be improve learning results IPA class IV MI Al-Muhairin Menggala Sakti?". The Research of Subject Class IV by twenty 20 students con sisting of thirteen 13 male and seven 7 female . The research results show that the Student complete basic fundamentals score that is 8 Student completed (40.00%), increase to cycle I became 14 students (70.00%), and increase again to cycle become 19 students (95.00% ). And I Cycle score Increased of 19.82%. Increases In Cycle II cycle on the average to 28.32%. Such data can be concluded that the model application of Quantum Learning Teaching can be improve learning results IPA class IV MI Al-Muhajirin Menggala Sakti. Key Words : Quantum Learning Model of Teaching, Learning Outcomes IPA